Distinct Bile Acid Signature in Parkinson's Disease With Mild Cognitive Impairment - Kun Nie; Yanyi Li; Yanyi Li; Jiahui Zhang; Yuyuan Gao; Yihui Qiu; Rong Gan; Yuhu Zhang; Lijuan Wang (Frontiers in Neurology, 2022)
BackgroundsBile acid (BA) plays a crucial role in various neurodegenerative diseases, including Parkinson's disease (PD). However, no clinical evidence supports BA's potential role in patients with PD with mild cognitive impairment (PD-MCI).ObjectivesThis study aimed at investigating the differential BA profile between patients with PD-MCI and those with normal cognitive function (PD-NC).MethodsUltra-high performance liquid chromatography-MS/MS was applied for BA quantitation. After between-group differences of the BA profile were addressed, orthogonal projections to latent structures—discriminant analysis (OPLS-DA) and the area under the receiver-operating-characteristic curve (AUC-ROC) were implemented for further verification.ResultsLower levels of chenodeoxycholic acid (CDCA), cholic acid (CA), and ursodeoxycholic acid (UDCA) were significantly associated with PD-MCI (p < 0.01 for both; VIP ≈ 2.67, 1.66, and 1.26, respectively). AUC-ROC were 78.1, 74.2, and 74.5% for CDCA, CA, and UDCA, respectively.ConclusionCA, CDCA, and UDCA might be distinct BA signatures for patients with PD-MCI.